Passenger to Frankfurt : An Extravaganza - Christie, Agatha, 1890-1976 (London HarperCollins Publishers, 1970)
A middle-aged diplomat is accosted in an airport lounge and his identity stolen...
Keywords: Detective and mystery stories, English -- Germany--Frankfurt am Main -- Detective and mystery stories